1992
DOI: 10.1093/oxfordjournals.humrep.a137550
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization of the naturally occurring analogues of intrapituitary human follicle-stimulating hormone

Abstract: In the present studies we analysed the main physicochemical and biological properties of the several isoforms of human pituitary follicle-stimulating hormone (hFSH). Extracts of total anterior pituitary glycoproteins from adult donors were submitted to chromatofocusing and several forms of immunoactive hFSH with isoelectric points (pI) ranging from 7.6 to 3.8 were identified. An additional isoform was detected after passing through the chromatofocusing column a 1.0 M NaCl solution (salt peak). Each hFSH isofor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 0 publications
0
42
0
Order By: Relevance
“…The main difference among the various isoforms is caused by charge, which in FSH is mainly determined by its content in terminal sialic acid residues (Chappel et al 1983, Baenzinger & Green 1988, Ulloa-Aguirre et al 1995, although differences in nonterminal carbohydrates also play an important role in determining the heterogenous nature of the several members of the glycoprotein hormone family (Ulloa-Aguirre et al 1988b, Papandreou et al 1993, Creus et al 1996. We and others have found that the receptor binding activity of the intrapituitary FSH isoforms varies depending on the charge of the isoform (Stanton et al 1992, Ulloa-Aguirre et al 1992, Yding Andersen et al 1999. Less acidic/ sialylated FSH isoforms exhibit lower dissociation constants than the more sialylated counterparts when assessed by heterologous receptor assay systems, which may explain the greater capacity of the former variants to stimulate oestrogen production by cultured granulosa cells (UlloaAguirre et al 1992, Zambrano et al 1999.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main difference among the various isoforms is caused by charge, which in FSH is mainly determined by its content in terminal sialic acid residues (Chappel et al 1983, Baenzinger & Green 1988, Ulloa-Aguirre et al 1995, although differences in nonterminal carbohydrates also play an important role in determining the heterogenous nature of the several members of the glycoprotein hormone family (Ulloa-Aguirre et al 1988b, Papandreou et al 1993, Creus et al 1996. We and others have found that the receptor binding activity of the intrapituitary FSH isoforms varies depending on the charge of the isoform (Stanton et al 1992, Ulloa-Aguirre et al 1992, Yding Andersen et al 1999. Less acidic/ sialylated FSH isoforms exhibit lower dissociation constants than the more sialylated counterparts when assessed by heterologous receptor assay systems, which may explain the greater capacity of the former variants to stimulate oestrogen production by cultured granulosa cells (UlloaAguirre et al 1992, Zambrano et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Although in both the pituitary gland and serum the relative proportion of highly acidic/sialylated isoforms predominates over that of the less sialylated forms, the latter variants substantially increase during the periovulatory period (Padmanabhan et al 1988, Wide & Bakos 1993, Zambrano et al 1995, Anobile et al 1998. As a consequence of their structural differences, FSH isoforms differ in their capability to bind to target-cell receptors, survive in the circulation and evoke biological responses (Ulloa-Aguirre et al 1988a, 1992, Yding Andersen et al 1999, Zambrano et al 1999. Highly acidic/sialylated isoforms have considerably longer plasma half-lives but more modest and/or slower capacities to elicit cellular responses in vitro and in vivo (Wide 1986, Ulloa-Aguirre et al 1992, Timossi et al 1998b, Vitt et al 1998, Yding Andersen et al 1999.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that gonadotropin isoforms influence a variety of biological activities, cellular growth and development, steroidogenesis and protein synthesis [37][38][39]. Because of their structural differences, FSH isoforms differ in their ability to bind to target cell receptors surviving in the circulation and induce a biological response in vivo and in vitro [40][41][42][43][44]. Evident differences between recombinant and urinary FSH were recognized, rFSH contains a higher proportion of less acidic isoforms, whereas urinary FSH contains a higher proportion of acidic forms.…”
Section: Discussionmentioning
confidence: 99%
“…The 92-amino acid ␣-chain and the 111-amino acid ␤-chain have each two Nlinked oligosaccharide chains presented as complex heterogeneous multiantennary structures (3). The variable degree of glycosylation, especially of sialylation, creates a spectrum of FSH isoforms with differences in charge, bioactivities, and elimination halflives (4,5).…”
mentioning
confidence: 99%